2002
DOI: 10.1128/iai.70.12.6652-6657.2002
|View full text |Cite
|
Sign up to set email alerts
|

Marked Enhancement of the Antigen-Specific Immune Response by Combining Plasmid DNA-Based Immunization with a Schiff Base-Forming Drug

Abstract: Although plasmid DNA (pDNA)-based immunization has proven efficacy, the level of immune responses that is achieved by this route of vaccination is often lower than that induced by traditional vaccines, especially for primates and humans. We report here a simple and potent method to enhance pDNA-based vaccination by using two different plasmids encoding viral or bacterial antigens. This method is based on coadministration of low concentrations of a recently described immunopotentiating, Schiff base-forming drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…It has recently been shown that tucaresol efficiently enhances the immune response to pDNA immunization (6). This was manifested as an increased humoral and cellular response to the mycobacterial heat shock protein 65 (Mhsp65) and Epstein-Barr virus nuclear antigen 4 (EBNA-4) genes determined using in vitro assays for antibody production, cytokine release, T-cell proliferation, and cytotoxicity.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It has recently been shown that tucaresol efficiently enhances the immune response to pDNA immunization (6). This was manifested as an increased humoral and cellular response to the mycobacterial heat shock protein 65 (Mhsp65) and Epstein-Barr virus nuclear antigen 4 (EBNA-4) genes determined using in vitro assays for antibody production, cytokine release, T-cell proliferation, and cytotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Other approaches to enhance DNA vaccination include the use of cytokine-encoding plasmids such as granulocyte-macrophage colony-stimulating factor, which has been shown to enhance the protective efficacy of an influenza DNA vaccine (21). Tucaresol was previously compared to gamma interferon and granulocyte-macrophage colony-stimulating factor for their efficiency as DNA vaccine adjuvants, and tucaresol was found to be at least as strong an adjuvant as either of these two cytokines (6). It has been shown that NP-based DNA immunization results in heterologous protection that is T-cell mediated (15,32).…”
Section: Vol 78 2004 Tucaresol Enhances Dna Influenza Virus Vaccinementioning
confidence: 99%
See 3 more Smart Citations